Experiences of recently HIV‐diagnosed gay and bisexual migrants in Australia: Implications for sexual health programmes and health promotion. (15th September 2022) - Philpot, Steven P.; Aung, Eithandee; Templeton, David J.; Stackpool, Gai; Varma, Rick; Power, Cherie; Robinson, Sharon; Stratigos, Alexandra; Mao, Limin; Grulich, Andrew E.; Bavinton, Benjamin R.
Abstract: Gay and bisexual migrants from low‐ and middle‐income countries living in high‐income countries are disproportionately diagnosed with HIV. Most research focuses on preventing HIV acquisition among HIV‐negative migrant gay and bisexual men (GBM). This study is uniquely positioned to report on migrant GBM's experiences and needs at and after an HIV diagnosis. Semi‐structured interviews were conducted with 24 migrant GBM diagnosed at sexual health clinics in Australia from 2017 onwards. Interviews were analysed using a codebook thematic analysis. Due to the stigma of HIV and homosexuality in their countries of origin, about half of participants had poor HIV knowledge prior to diagnosis. Absorbing diagnosis information was consequently difficult, and feelings of shame, hopelessness, lost sexual opportunities and infectiousness were common. However, many were thankful for the comprehensive clinical support they received and believed that over time life would 'normalise' with sustained undetectable viral load. None reported that their clinician stigmatised them, but the anticipation of stigma nonetheless infused their experiences after diagnosis. Many were selective about HIV disclosure, and some mentioned that clinic systems posed a risk to confidentiality. Non‐permanent residents were concerned about the impacts of HIV status on future visa applications. We recommend that newly HIV‐diagnosed migrant GBM receive referral to legal and culturally appropriate migration services to help absorb what a diagnosis might mean for their health and visa status. We also recommend sexual health clinics continue to assess confidentiality in their systems. Health promotion initiatives should highlight to migrant GBM that high‐HIV caseload sexual health clinicians provide confidential and comprehensive care.